Indonesia ANALISIS KOMPARASI PROSEDUR PELAKSANAAN HUKUMAN MATI INDONESIA DAN THAILAND: Comparative Analysis Of Death Penalty Implementation Procedures In Indonesia And Thailand - Calvino Endryan; Abdul Ficar Hadjar (Reformasi Hukum Trisakti, 2024)
In Indonesia, the death penalty is carried out by an execution team, following regulations outlined in Presidential Decree No. 2 of 1964 on the Execution Procedure of the Death Penalty by General and Military Courts, and National Police Chief Decree No. 12 of 2010 on the Implementation Procedure of the Death Penalty. In contrast, Thailand administers the death penalty through lethal injection, based on the Thai Penal Code B.E. 2499, 1956. The formulation of this research problem is the similarities and differences in the implementation of the death penalty in Indonesia and Thailand, and the weaknesses and strengths of the implementation of the death penalty in Indonesia and Thailand. The research was carried out using a normative juridical research method, using secondary data which collected data through literature study and qualitative analysis. The research results show that the death penalty regulations in Indonesia and Thailand have similarities and differences. Similarities include procedures before carrying out an execution and differences regarding the execution. And the research results illustrate the weaknesses and strengths of the implementation of the death penalty between Indonesia and Thailand which can be used as an evaluation for the two countries.